Efficacy of Fungicides for Control of White Mold (Sclerotinia sclerotiorum Lib.) De Bary in Lima Bean - Pandey, Ashutosh; Mathew, Amita J; Kamle, Madhu; Mishra, Rupesh Kumar; Kumar, Pradeep (Journal of Horticultural Sciences, 2012)
White mold of lima bean (Phaseolous lunatus) caused by Sclerotinia sclerotiorum is a major disease in India. Isolates of the pathogen from different region of Uttar Pradesh were assayed both in vitro and in the greenhouse (in vivo) for their sensitivity to eight commercially available fungicides, viz., dithiocarbamic acid, carbendazim, ziram, phenylthiourea, carboxin + dithiocarbamic acid, difenoconazole, hydrogen sulphide, and mancozeb. Phenylthiourea and difenoconazole were found to be most effective and these inhibited radial growth of the test organism a level of to 71.5% and 70.5%, respectively. These two fungicides were also found as most promising in controlling the disease under greenhouse conditions, reducing disease severity to 0.14% and 0.22%, respectively compared to the control where it was 18.9%.